Physical consolidation of rattan furniture waste fibers in self-bonded boards under morphological analysis - Halim, Zahurin; Ahmad, Zuraida; Tajuddin, Maisarah (Microscopy Society of Malaysia, 2020)
High concerns on the health risks and environmental issues owing to the usage of synthetic resin had revolved the alternative on fabricating producing self-bonded boards, by utilizing rattan furniture waste (RFW) as the main material. These boards were hot-pressed with pressing parameters of 1.5MPa, 180oC and 5 minutes. This study focuses on analyzing the self-bonding mechanism occurred among the fibers inside the boards, under Scanning Electron Microscope (SEM) with 100x magnification. RFW had good deformation ability of cell wall due to the high dimension ratio of lumen to cell wall and flexibility of parenchyma cells when being pressed. These factors enhanced the physical consolidation of fibers, and improved the inter-fiber bonding. The disorientation of fibers and fiber surface might affect the properties of self-bonded boards produced. Thus, sufficient pressing pressure and pressing temperature must be applied to ensure resilient physical consolidation of fibers to produce good quality self-bonded boards.